(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Millennial generation, starting from twelve-year-olds up to adolescents, is one of the most complicated generational cohorts; its ecosystem, beyond of formal and non-formal education boundaries, is more diverse than for any other previous generation. Digital learners prefer a digital learning environment, as the advantage of digital learning is the control over time, place, way and pace, enabling you to impersonate as an educational institution, applying smart personal network which consists of 3 domains: applied smart technologies; reflexive pedagogy for the digital century [1]; learning environment [2], thus without any confrontation of formal and non-formal education, but rather with consolidation of resources to promote engineering development of formal environment at school, higher educational establishments and informal activities – projects, scientists’ night events, open days, interest-related education programmes, etc.Goal of the research is to analyse the proposal of formal and non-formal education for the new generation digital learning demand and identify the examples of good practice in engineering, based on the identified digital leaning criteria obtained as a result of theoretical analysis. Millennial generation, starting from twelve-year-olds up to adolescents, is one of the most complicated generational cohorts; its ecosystem, beyond of formal and non-formal education boundaries, is more diverse than for any other previous generation. Digital learners prefer a digital learning environment, as the advantage of digital learning is the control over time, place, way and pace, enabling you to impersonate as an educational institution, applying smart personal network which consists of 3 domains: applied smart technologies; reflexive pedagogy for the digital century [1]; learning environment [2], thus without any confrontation of formal and non-formal education, but rather with consolidation of resources to promote engineering development of formal environment at school, higher educational establishments and informal activities – projects, scientists’ night events, open days, interest-related education programmes, etc.Goal of the research is to analyse the proposal of formal and non-formal education for the new generation digital learning demand and identify the examples of good practice in engineering, based on the identified digital leaning criteria obtained as a result of theoretical analysis. In the design research of cross-sectional study 323 respondents took part: 226 representatives of formal education and 97 representatives of non-formal education. In the research the quantitative and qualitative data collection (questionnaires, case analysis) and processing (nonparametric software in SPSS environment and content analysis) methods have been applied. Results of Mann-Whitney U-test to two independent samples confirm statistically significant differences depending on the respondents’ profile: representatives of non-formal education tend to value Higher such digital learning criteria as situational and authentic, whereas representatives of formal education value higher interactive digital learning on demand, which is related to application of different media platforms (p≤0.05).The research analyses the examples of good practice in case studies in engineering.Engineering can be geared towards fundamental research, but in the pupils’ educational process the innovative solutions of technical sciences with a perspective of practical applicability arouse a greater interest. Learning efficiency and acquisition of new knowledge are successful if learning is linked to research work in higher educational establishments and transfer of findings in the education system in close collaboration with representatives of economic sectors and businesses.